Adaptive reuse of heritage architecture and its external effects on sustainable built environment—Hedonic pricing model and case studies in Hong Kong. (13th September 2020) - Kee, Tris; Chau, Kwong Wing
Abstract: The integration of the sustainable development perspective into the discussion of heritage conservation by UNESCO in 2015 represents an acknowledgement of the values of heritage conservation in the agenda of sustainable development. This paper aims to provide empirical evidence regarding how heritage conservation fits into the overall sustainable development in Hong Kong by examining the external effects generated by architectural heritage conservation onto their adjacent neighborhood. By two adaptive reuse heritage case studies with respective hedonic pricing analysis on their adjacent property prices, this paper presents the results of how residential property prices have been increased as a result of heritage adaptive reuse. The analysis suggests that an established heritage grading mechanism along with a socially inclusive conservation approach with community stakeholders not only maintains the authenticity of the cultural heritage, but also brings substantial social and economic benefits to the neighboring communities. The research findings add new knowledge to the studies on sustainable development and provide practical recommendations to policymakers, urban planners, and heritage conservationists in future heritage policy and implementation.